Monitoring of micro-deformations along Idrija and Raša faults in W Slovenia - Gosar, Andrej (Geologija, 2007)
Monitoring of tectonic movements along two active faults of Dinaric (NW-SE trending) fault system in W Slovenia using TM 71 extensiometers was set up in 2004. After two years ob measurements some clear trends of displacement were developed. The average left-lateral displacement along a crack in the inner fault zone of the Idrija fault in Učja valley is 0.38 mm/year. Short term (10 months) rates were even greater and reached the value of 0.54 mm/year. Since the Idrija fault is considered as dextral strike-slip, is the observed left-lateral displacement explained by local piermutation of principle stress axis. In the Raša fault monitoring site at the foot of Vremščica Mt. at Košana the average reverse uplift of hanging wall (SW) block of 0.24 mm/years and left-lateral displacement of 0.16 mm/year were established. Short term (9 months) vertical displacements reached the value of 0.53 mm/year. The oblique sense of displacement is in agreement with geological and seismological observations. Since there were no stronger earthquakes in the vicinity and time span of monitoring, no correlations were established with seismic activity. The observed displacement rates along monitored faults of up to 0.5 mm/year are consistent with the regional deformation rate in W Slovenia established from GPS measurements which is of the order of 2 mm/year.